2021
DOI: 10.3390/ijms22115793
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review: Sphingolipid Metabolism and Implications of Disruption in Sphingolipid Homeostasis

Abstract: Sphingolipids are a specialized group of lipids essential to the composition of the plasma membrane of many cell types; however, they are primarily localized within the nervous system. The amphipathic properties of sphingolipids enable their participation in a variety of intricate metabolic pathways. Sphingoid bases are the building blocks for all sphingolipid derivatives, comprising a complex class of lipids. The biosynthesis and catabolism of these lipids play an integral role in small- and large-scale body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
145
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 278 publications
1
145
0
5
Order By: Relevance
“…1a) . Because sphingosines are generated by degradation of more complex sphingolipids 13 , their reduced levels suggest that degradation of sphingolipids is impaired in PGRN-deficient brains. Unlike sphingolipids, levels of the phospholipids phosphatidylethanolamine (PE), phosphatidylcholine (PC), PS, and of neutral lipids were similar among genotypes ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a) . Because sphingosines are generated by degradation of more complex sphingolipids 13 , their reduced levels suggest that degradation of sphingolipids is impaired in PGRN-deficient brains. Unlike sphingolipids, levels of the phospholipids phosphatidylethanolamine (PE), phosphatidylcholine (PC), PS, and of neutral lipids were similar among genotypes ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The closest association of sphingolipids with neurodegenerative diseases was related to their structural function, especially the glycosphingolipids, as the main component of the plasma membrane of oligodendrocytes and myelin [9]. However, several studies have demonstrated the implication of sphingolipids in several key biological processes such as cellular proliferation and migration, differentiation, autophagy, apoptosis, senescence, and inflammation [8,[10][11][12][13][14]. Recent works on transcriptomics and electrospray ionization mass spectrometry analysis (sphingolipidomics) have demonstrated the variation of specific levels of sphingolipids and enzymes involved in their metabolism in different neurodegenerative diseases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, ceramide species can induce endothelial dysfunction and increase vascular permeability by promoting oxidative stress, inflammation and by reducing the production of nitric oxide (NO) [40]. Therefore, ceramides are important regulators of tissue metabolism and play vital roles in pathophysiological processes with implications in cardiometabolic disease such as ATS [41], inflammation, obesity, NAFLD [42], pancreatic ß-cell dysfunction, T2DM [43], and cancer [44].…”
Section: Ceramides In Nafld-ats Developmentmentioning
confidence: 99%
“…Regarding their involvement in atherogenesis, they participate by two mechanisms: one directly on the vascular wall through transcytosis of ox-LDL, and second through insulin sensitivity and dyslipidemia [44]. In different circumstances, data shows that ox-LDL is present in the atherosclerotic plaque, and that increased blood concentration especially in patients with NAFLD, mediates activation of LacCer synthase and thus, the development of ATS [45,46].…”
Section: Ceramides In Nafld-ats Developmentmentioning
confidence: 99%